BEYOND E-PRIME. - Parkinson, Theresa (ETC: A Review of General Semantics)
Examines the debate over the use of E-Prime. False identification; Morality and reason; Benefits of E-Prime as an intellectual exercise; Change in language and changing perceptions; Restructuring verbal communication; More.